Bone marrow adiposity inversely correlates with bone turnover in pediatric renal osteodystrophy - Ornatcha Sirimongkolchaiyakul; Renata C. Pereira; Barbara Gales; Justine Bacchetta; Isidro B. Salusky; Katherine Wesseling-Perry (Bone Reports, 2021)
Bone marrow adiposity is associated with bone disease in the general population. Although chronic kidney disease (CKD) is associated with increased bone fragility, the correlation between marrow adiposity and bone health in CKD is unknown. We evaluated the relationship between bone marrow adipocytes and bone histomorphometry in 32 pediatric patients. We also evaluated the effects of growth hormone and calcitriol (1,25(OH)2D3)—two therapies commonly prescribed for pediatric bone disease—on marrow adiposity and bone histomorphometry. Finally, the adipogenic potential of primary human osteoblasts from CKD patients was assessed in vitro, both alone and in the presence of 1,25(OH)2D3. In cross-sectional analysis, marrow adipocyte number per tissue area (Adi.N/T.Ar) correlated with bone formation rate/bone surface (BFR/BS) in patients with high bone turnover (r = −0.55, p = 0.01) but not in those with low/normal bone turnover. Changes in bone formation rate correlated with changes Adi.N/T.Ar on repeat bone biopsy(r = −0.48, p = 0.02). In vitro, CKD and control osteoblasts had a similar propensity to transition into an adipocyte-like phenotype; 1,25(OH)2D3 had very little effect on this propensity. In conclusion, marrow adiposity correlates inversely with bone turnover in pediatric patients with high turnover renal osteodystrophy. The range of adiposity observed in pediatric patients with low/normal bone turnover is not explained by intrinsic changes to precursor cells or by therapies but may reflect the effects of circulating factors on bone cell health in this population.